Comparison of Rail Freight Transportation Markets in Lithuania and Poland. (2017) - Jaržemskis, Andrius; Jaržemskienė, Ilona
Abstract: The objective of the article is to compare rail freight markets in Lithuania and Poland. The comparison is mainly focused on rail and road transport competition in various freight segments – oil, fertilizers, grain, coal and minerals as well as palletized cargo in both countries. The serious differences are obtained in separate freight segments. For instance oil and oil d products are so called as "rail-borne freight" in one Lithuania. The same freight segments are mainly served by roads in Poland. The pricing levels, average transportation distance, the competition within railway market are also taken into account to compare both countries. The main outcome of the article would be very valuable when Rail-Baltica project will be finished and Lithuanian and Poland rail freight market would be fully integrated.